Uncovering the Nexus of Identity and Forced Migration: A Collaborative Autoethnographic Study of Afghan Women’s Experiences in Diaspora - Hashemi, Narjes; Amiry, Safia (Comparative and International Education / Éducation comparée et internationale, 2024)
This qualitative research investigates the educational mobility of Afghan women in the diaspora, particularly those who have experienced forced migration following the Taliban’s takeover of Afghanistan in 2021. The study delves into how their intersectional identities, including gender, ethnicity, religion, and socioeconomic status, shape their educational experiences. These Afghan women’s educational journeys are further complicated by the challenges posed by political and economic conditions in refugee communities, which limit their access to education and employment opportunities while increasing the risk of discrimination and violence. Using a collaborative autoethnographic approach, we leverage our personal experiences as Afghan women who immigrated to Canada during two distinct Taliban occupation eras. Through self-reflection, journaling, and daily life observation, we provide nuanced insights into the multifaceted challenges faced by Afghan women during their forced displacement and migration.